EVALUASI PENERAPAN TINGKATAN BIOSEKURITI PADA PETERNAKAN AYAM PETELUR DI KABUPATEN BOJONEGORO JAWA TIMUR - Lia Nur Aini; Khoirul Huda; Hamzah Nata Siswara; Teguh Dwi Putra; Fajar Zeti Oktavia (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
This research method is using observation and survey with a quitionnaire to collect data. It is intended to get an overview of the farmer answer. Quitionnaire model using lingkert scale by category. The category is ‘accordance’ (skore:2), ‘adequat’ (skore:1), and ‘not accordance’ (skore:0). Characteristic of farmer based on data is gender, age, last education, production time, number of bird, phase of bird, ownership, and breeding production. Evaluate of biosecurity levels are conseptual biosecurity, structural biosecurity, and operational biosecurity as fixed variable as according to shane’s opinion (2005). The conclusion of this research is average of the percentage of farmers carrying out biosecurity activities is adequate in the conceptual biosecurity of 76%, structural biosecurity 66% and operational biosecurity 66%. Keywords: Laying hens, Biosecurity, Livestock